Correlation between Neutrophil to Lymphocyte Ratio with C-Reactive Protein Levels in COVID-19 Patient - Wiratmoko, Mirsyam Ratri; Hajarani, Fityaya (Muhammadiyah Medical Journal, 2024)
Background: Coronavirus Disease 2019 (COVID-19) is an infectious disease brought on by SARS-CoV-2. China's Hubei Province's Wuhan City is where the pandemic first began. The number for Indonesia is 1,790. Neutrophil Lymphocyte Ratio (NLR) and C-reactive protein (CRP) tests are conducted to assess the disease prognosis in COVID-19 patients, who may have a bad prognosis. Purposes: To find out the relationship between NLR and CRP in COVID-19 patients at Bunda Margonda General Hospital in 2021. Method: This study used an analytic observational method with a cross-sectional approach and used secondary data from 100 samples from COVID-19 patients' medical records at Bunda Margonda General Hospital in 2021. Results: More COVID-19 patients were found in 56 male patients, aged 46-55 years, with 22 patients; NLR values increased in 67 patients and 80 patients in CRP. There is a significant relationship between NLR and CRP in COVID-19 patients at Bunda Margonda General Hospital in 2021, with a p-value of 0.001. The most common COVID-19 cases were found in male patients 46-55 years of age, and there was an increase in the NLR and CRP values. Conclusion: There is a relationship between NLR and CRP in COVID-19 patients at Bunda Margonda General Hospital in 2021.